Trade and Financial Development - Do, Quy-Toan; Levchenko, Andrei A. (World Bank, Washington, D.C., 2013)
The differences in financial development between advanced and developing countries are pronounced. It has been observed, both theoretically and empirically, that these differences in countries' financial systems are a source of comparative advantage and trade. This paper points out that to the extent a country's financial development is endogenous, it will in turn be influenced by trade. The paper builds a model in which a country's financial development is an equilibrium outcome of the economy's productive structure: in countries with large financially intensive sectors financial systems are more developed. When a wealthy and a poor country open to trade, the financially dependent sectors grow in the wealthy country, and so does the financial system. By contrast, as the financially intensive sectors shrink in the poor country, demand for external finance decreases and the domestic financial system deteriorates. This paper describes the authors' test model using data on financial development for a sample of 77 countries. The authors find that the main predictions of the model are borne out in the data: trade openness is associated with faster financial development in wealthier countries, and with slower financial development in poorer ones.